Assessing Direct Digital Services Taxes in Africa: Compliance with the Canons of Taxation - Nabiebu, Miebaka; Ekpo, Mokutima Etido; Anukanti, Vivien Chioma; Agube, Ntamy (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
The rapid expansion of the digital economy has introduced complexities in tax revenue mobilization, particularly in the taxation of digital transactions, both domestic and international. The intangible nature of digital services has facilitated tax evasion and avoidance, prompting governments worldwide to formulate policies aimed at capturing revenue from this sector. African countries are no exception, having introduced various digital tax policies, including both direct and indirect taxes. This paper focuses on Direct Digital Services Taxes (DSTs), which have sparked considerable debate among governments, policymakers, academics, tax bodies, and development organizations. Discussions primarily revolve around their structural design, compliance with the canons of taxation, potential benefits and challenges, and their broader economic implications. Through a literature review, this study examines the legislative frameworks and administrative approaches to DSTs in Africa, assessing their alignment with fundamental taxation principles. The findings reveal mixed outcomes. While some aspects of DSTs align with taxation principles such as fairness and efficiency, others conflict with them. These inconsistencies can be attributed to differences in economic structures, political environments, and administrative capacities across African nations, as well as disparities between developing and developed economies. The study concludes that while DSTs are crucial for harnessing revenue from the digital economy, their design and implementation must carefully balance equity, neutrality, efficiency, and economic viability to ensure optimal tax policy outcomes.